Torn thread - Isaacs Anne 1949-; Anne Isaacs (New York : Scholastic, 2000)
In an attempt to save his daughter's life, Eva's father sends her from Poland to a labor camp in Czechoslovakia where she and her sister survive the war.
Q
880